Low-cost biomimetic sensor based on copper porphyrin-modified graphite electrodes for electrochemical detection of glyphosate in aqueous samples - Janeiro Tudanca, Ana Maria (2025)
We present a biomimetic electrochemical sensor for glyphosate (GLY) detection, utilizing graphite electrodes modified with electropolymerized copper(II) meso-tetra(4-sulfonatophenyl)porphyrin (CuP). The Cu(II) centers provide dual functionality: catalytic oxygen reduction and selective GLY coordination, which leads to a proportional suppression of redox currents. Characterization (SEM-EDS/Raman/UV-Vis) confirmed CuP polymerization and specific GLY binding. The sensor achieved a 1 μmol L−1 detection limit (S/N = 3) with linear response (2–120 μmol L−1; RSD = 0.7%) and >98% recovery in spiked rainwater. Stability tests showed 99% signal retention after 30 days, outperforming enzyme-based sensors. This platform combines three key advantages: (1) sustainable fabrication ($0.12/electrode), (2) rapid analysis (<5 min per sample), and (3) field-deployability without instrumentation. The nanostructured CuP film improves sensitivity and contributes to selective GLY detection by excluding common interferents (nitrate/humic acid). Compared to chromatographic methods, this approach offers an eco-friendly alternative for environmental GLY monitoring.